1995
DOI: 10.1159/000217925
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Functions for Two Classes of Genes of the Human Carcinoembryonic Antigen Family

Abstract: The human carcinoembryonic antigen (CEA) family can be divided into two subgroups according to the means of anchorage of member glycoproteins to the cell membrane: glycophos-phatidyl inositol (GPI) linkage and transmembrane linkage. The GPI-linked members tend to be up-regulated in human tumours, whereas the transmembrane-linked members tend to be down-regulated. Thus the question as to whether the GPI members could be formally considered to function as onco-genes and the transmembrane members as tumour suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…The avidity of adhesion was also reduced if the A2 domain was removed from the CEACAM1-4 soluble molecule. Whereas previous studies have shown that cells expressing CEACAM1-4L and -4S are able to mediate homophilic adhesion, 6,[64][65][66][67] our studies show that CEACAM1-4S in contrast to CEACAM1-4L transfectants bind less avidly to immobilized CEACAM1 molecules and suggest that the IgC2 and cytoplasmic domains of CEACAM1 may regulate the specificity and avidity of homophilic and heterophilic interactions or signaling functions. Several observations support this view.…”
Section: Org Fromcontrasting
confidence: 80%
“…The avidity of adhesion was also reduced if the A2 domain was removed from the CEACAM1-4 soluble molecule. Whereas previous studies have shown that cells expressing CEACAM1-4L and -4S are able to mediate homophilic adhesion, 6,[64][65][66][67] our studies show that CEACAM1-4S in contrast to CEACAM1-4L transfectants bind less avidly to immobilized CEACAM1 molecules and suggest that the IgC2 and cytoplasmic domains of CEACAM1 may regulate the specificity and avidity of homophilic and heterophilic interactions or signaling functions. Several observations support this view.…”
Section: Org Fromcontrasting
confidence: 80%
“…Since only TM-anchored CEACAM1-like genes have been discovered in rodents, we and others have suggested a recent evolution of GPI-anchored CEA family members from a primordial TM-anchored gene (Hammarström et al, 1998;Stanners et al, 1995;Stanners et al, 1992;Zimmermann, 1998). In view of the rather dramatic changes in function implicated by the acquisition of the GPI anchor (see Introduction), we decided to examine the ease of derivation of GPI linkage from the TM domain of present-day human CEACAM1.…”
Section: Discussionmentioning
confidence: 97%
“…MHVR1 (mmCGM1) and MHVR2 (mmCGM2) have been reported to exhibit cell adhesion activity, though the properties of this activity are different between these two proteins; the adhesion activity of mmCGM1 works in a calcium-and temperature-dependent manner, while that of mmCGM2 is calcium-and temperature-independent (McCuaig eta]., 1992; Turbide eta]., 1992). The adhesion activity of mmCGM1 and mmCGM2 could be mediated by the N domain located at the N terminal region of the molecules as shown in human BGP (Stanners et al, 1995;Teixeira eta]., 1994). The same domain of the molecule interacts with the N-terminal region of the MHV S protein (Dveksler eta[., 1993 b;Kubo eta[., 1994).…”
Section: Discussionmentioning
confidence: 98%